The bachelor of medicine and bachelor of surgery program for international students in China: policies, assessments and challenges - Huang, Zheng (Frontiers in Medicine, 2025)
Internationalization of medical education (IoME) in China is an integral part of the broader higher education internationalization efforts, a process that has been strategically designed and implemented by the Chinese government since the introduction of the opening-up policy in the late 1970s. The bachelor of medicine and bachelor of surgery (MBBS) program, a 6-year English medium undergraduate program with an international curriculum for overseas medical students, provides a new perspective on the IoME in China. This paper expounds on the national policy development of the IoME and MBBS program, summarizes the assessments of the program, and highlights the challenges arising from students (e.g., selection and support), curricula (e.g., curriculum integration) and faculties (e.g., faculty improvement) that constitute the core of the 3-dimensional model of the IoME. Improving the quality of the MBBS program would contribute to building a brand project of the IoME in China and balancing the medical workforce supply at the regional and global levels.